Understanding the Terminal Velocity of Particle Motion in Fluids at the Senior High School Level with Numerical Experiments - Hun, Hilarius Donatus; Fahra, Raden Manzilah Mubarokah; Putri, Bella Yunisah; Aufia, Yasrifa Fitri; Jubaedah, Jubaedah (International Journal of STEM Education for Sustainability, 2024)
Investigating the motion of solid particles in fluids analyzes the drag force experienced by the particles, depending on parameters such as particle diameter, fluid velocity, density, and viscosity. The Reynolds number, which expresses a fluid's inertia relative to its viscosity, governs the dimensionless drag coefficient, which is critical to understanding drag forces. Terminal velocity, achieved when the force of gravity equals the buoyancy and drag forces of the fluid, is a critical concept often analyzed using the Stokes model. However, differences between theoretical and experimental terminal velocities arise due to oversight of the model's application conditions. Numerical experiments offer controlled conditions to address this, helping predictions align with theoretical models. This research explores the influence of density ratio and particulate diameter on terminal velocity, aiming to support research-based learning for teachers and conceptual understanding for students. Numerical experiments designed by Arbie et al. (2021) investigated two-dimensional particulate configurations, allowing controlled manipulation of parameters. The results show a strong influence of the density ratio and diameter to the terminal velocity, with larger parameter values influencing the Reynolds number and giving rise to differences between theoretical and experimental values. Therefore, careful parameter selection is essential for viscosity experiments, aligning with the objectives and comparability of theoretical models.